Reframing the PhD for Australia's future universities : final report. - Barrie, Simon; Fyffe, Jeanette; Graffam, Joe; Kwan, Alistair; McCallum, Peter; Partridge, Lee; Peseta, Tai; Trigwell, Keith (Australia. Dept of Education and Training (DET), 2018)
This project addresses the role of the PhD in preparing the academic workforce of the future, especially in relation to higher education teaching. It is a direct response to the key recommendations contained in the Office of Learning and Teaching (OLT) report by Probert (2014) on the relationship between current forms of doctoral training and the demands of academic work, and particularly the work of university teaching, which has been subject to remarkably little scrutiny. It pays particular attention to the preparation of doctoral students for careers in academia, but it does so in ways that will also better prepare doctoral students for careers in industry, and other areas of employment. One of the aims of this project was to provide resources for a different, academic-led, sector-wide conversation about renewing the PhD as a pathway to academic practice. The five appended briefing papers provide both background and detail on a proposed new direction for future development of the Australian PhD. This project has involved engagement across states, with supervisors and students, and members of academic research committees. It has made use of resources in a variety of ways, redesigned milestones in considering how the PhD and students' learning experience contributes to the knowledge network in Australia. While the outcomes represent a paradigm change for PhD education, they also offer a blueprint for new ideas about embedding employability preparation more generally. [Executive summary, ed]